Potensi ekowisata air terjun empare Desa Bungkang Kecamatan Sekayam Kabupaten Sanggau Provinsi Kalimantan Barat - Caroline Gracia; Agus Ruliyansyah; Pratita Budi Utami (Jurnal Arsitektur Lansekap, 2025)
Empare waterfall is a natural tourist destination  in Bungkang Village, Sekayam District, Sanggau Regency, West Kalimantan. it has many water areas with preserved natural beauty, including Empare Waterfall. Empare Waterfall is a natural spring that supplies the water needs of Bungkang residents. This research aims to determine the value of the ecotourism potential of Empare Waterfall as an ecotourism area using Tourist Attraction Object Analysis (ODTWA) and the Tourism Suitability Index (IKW) as the methods. The research results showed the lowest percentage of feasibility was obtained by the accommodation variable (50%), followed by the accessibility variable (67%), infrastructure & facilities (75%), and attractiveness (83%). The availability of clean water received the highest score (97%). The Tourism Suitability Index assessment result show a relatively high IKW score of 2,7 (very appropriate). A few spesies of wild animals/plants for education, such as the corpse flower or the titan arum flower, the pitcher plant flower, the horn bill, and the flyring lemur. Besides the species, Gawai Nasi Baru is a local culture that attracts tourists, They will support the ecotourism regime. This research develops an attraction distribution map as a recommendation for ecotourism tools.